Building coalitions: The interconnections between feminism and trans* activism in Spain. Issue 1 (2nd January 2016) - Lucas Platero, R.; Ortega-Arjonilla, Esther
Abstract: What made current Spanish feminism shift toward transfeminism? Based on in-depth interviews and literature reviews, we explore what factors facilitated the participation of trans* women in Spanish feminism. Tracing the history through relevant events such as the National Feminist Conferences, it becomes clear that trans* women participated in the 1993, 2000, and 2009 conferences, posing relevant issues regarding prostitution, transgenderism, and the political subject of feminism. Our research allows a break with global oppositional narratives, in which these movements are in conflict, and highlights the importance of understanding the vernacular nuances that take place in a particular geopolitical context.